A Case of Concurrent Gastric and Pancreatic Plasmacytomas in a Patient With Multiple Myeloma: An Extremely Rare Entity. (22nd May 2018) - Sunkara, Tagore; Sharma, Santosh R.; Ofosu, Andrew; Gaduputi, Vinaya; Reddy, Madhavi; Shahzad, Ghulamullah
Multiple myeloma (MM), a plasma cell tumor, is primarily a disease of the bone marrow. Extramedullary plasmacytoma, also a plasma cell tumor, is very rare in the gastrointestinal tract and the pancreas, and only a handful cases have been documented till now. Gastric and pancreatic plasmacytomas are usually seen in elderly patients; however, cases in patients as young as 32 years of age have been reported. Commonly, patients with gastric plasmacytoma present with nonspecific symptoms like epigastric pain, abdominal fullness, anorexia, and weight loss, or serious conditions like massive upper gastrointestinal bleeding and gastric outlet obstruction. Patients with pancreatic plasmacytoma commonly present with obstructive jaundice. In this article, we present the case of a 79-year-old man with a history of MM for 3 years, diagnosed with gastric and pancreatic masses, which turned out to be plasmacytomas. To our knowledge, simultaneous occurrence of gastric and pancreatic plasmacytomas is extremely uncommon with less than 5 cases reported in the literature. We also compiled all the individual cases of gastric and pancreatic MM that have been reported in literature till now.